Let me be Frank with you - Ford, Richard, 1944- (Ford, Richard, 1944- Frank Bascombe book., 2014)
Ford reinvents Bascombe in the aftermath of Hurricane Sandy. In four richly luminous narratives, Bascombe attempts to reconcile, interpret and console a world undone by calamity. It is a moving and wondrous and extremely funny odyssey through the America people live in at this moment.